2014
DOI: 10.1177/2042533313512480
|View full text |Cite
|
Sign up to set email alerts
|

Medical student syndrome: fact or fiction? A cross-sectional study

Abstract: ObjectivesIt is often reported by medical practitioners that medical students develop hypochondriacal concerns and symptoms relating to diseases they are studying, a phenomenon labelled ‘medical student syndrome’. However, the evidence that this syndrome exists and particularly that it contributes to an increased number of consultations (as typical hypochondriasis does) is weak. The present study investigates this phenomenon in terms of differences between medical and non-medical students in help-seeking behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 18 publications
0
44
0
2
Order By: Relevance
“…Simultaneously, they constantly worry about spreading infection to their families or partners, similar to the general public. As can be seen in the medical students' syndrome, those who lack practical experience in the field are more vulnerable to worrying about diseases due to their inadequate knowledge of diseases or symptoms ( 6 ). As COVID-19 continues to progress, medical students are forced to overcome the fear of an uncertain disease and simultaneously face the difficulties of working in hospitals just like other medical personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, they constantly worry about spreading infection to their families or partners, similar to the general public. As can be seen in the medical students' syndrome, those who lack practical experience in the field are more vulnerable to worrying about diseases due to their inadequate knowledge of diseases or symptoms ( 6 ). As COVID-19 continues to progress, medical students are forced to overcome the fear of an uncertain disease and simultaneously face the difficulties of working in hospitals just like other medical personnel.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that the risk for developing health anxiety is increased in medical students is old and its formulation was based on clinical teacher’s reports claiming that medical students frequently develop worries and symptoms of illness ( 5 , 6 ). Medical students experience a combination of stress and clinical knowledge which may cause them to overestimate the importance of insignificant symptoms and bodily sensations leading and tend to diagnose themselves with the diseases they are studying ( 7 , 8 ). Moreover, medical training is a demanding and stressful process which may have adverse impacts on the student’s mental health including anxiety and depression ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Present study shows observed characteristics of fear or phobia after reading about diseases having strong significance for medical students than non medical students. However research has shows that medical college causes students to experience a large amount of psychological pressure due to the work required, the stress of examinations, the anxiety associated with new clinical experiences and the competitive environment [14] . This may be the cause of slight higher percentage IAD and SSD among medical students than non medical.…”
Section: Resultsmentioning
confidence: 99%